2023
DOI: 10.21425/f5fbg58189
|View full text |Cite
|
Sign up to set email alerts
|

Birds and barriers: present and past seas are dominant correlates of avian turnover in the Indo-Australian Archipelago

Abstract: The Indo-Australian Archipelago (IAA) is a geologically dynamic area of high biotic endemism that spans the continental shelves of Sunda and Sahul and intervening oceanic islands. We provide a comprehensive quantitative assessment of how bird communities are structured across the IAA using beta diversity indices. We focus on three key questions. Are the islands of Wallacea a biogeographically cohesive unit or a more heterogeneous transition zone? Is the rich biota of New Guinea and the East Melanesian islands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…For example, we see many assemblages with high PD SES across the Indo-Australian archipelago, in the Wallacean islands between the Sunda and Sahul continental shelves, probably the most well-known contact zone between two regions with evolutionary distinct fauna (Holt et al, 2013). Recent phylogenetic and biogeographical studies have suggested that crown Passerines first radiated in what is now Australia and New Zealand ~47 Ma and then dispersed into the rest of the world via the island uplifting in Wallacea ~20-30 Ma (Moyle et al, 2016;Oliveros et al, 2019) and birds in the region show a highly complex biogeographic history of exchange and colonization dynamics across lineages (Prasetya et al, 2023).…”
Section: Regions Of Exceptional Mpfd and Pdmentioning
confidence: 99%
“…For example, we see many assemblages with high PD SES across the Indo-Australian archipelago, in the Wallacean islands between the Sunda and Sahul continental shelves, probably the most well-known contact zone between two regions with evolutionary distinct fauna (Holt et al, 2013). Recent phylogenetic and biogeographical studies have suggested that crown Passerines first radiated in what is now Australia and New Zealand ~47 Ma and then dispersed into the rest of the world via the island uplifting in Wallacea ~20-30 Ma (Moyle et al, 2016;Oliveros et al, 2019) and birds in the region show a highly complex biogeographic history of exchange and colonization dynamics across lineages (Prasetya et al, 2023).…”
Section: Regions Of Exceptional Mpfd and Pdmentioning
confidence: 99%